Late Onset Postcapillary Pulmonary Hypertension in Patients With Transposition of the Great Arteries and Mustard or Senning Baffles. Issue 10 (12th October 2017) - Chaix, Marie‐A.; Dore, Annie; Mercier, Lise‐Andrée; Mongeon, François‐Pierre; Marcotte, François; Ibrahim, Réda; Asgar, Anita W.; Shohoudi, Azadeh; Labombarda, Fabien; Mondésert, Blandine; Poirier, Nancy; Khairy, Paul
Abstract : Background: There is a paucity of data regarding late‐onset pulmonary hypertension (PH) in patients with transposition of the great arteries and atrial switch surgery. Methods and Results: A retrospective cohort study was conducted on 140 adults with transposition of the great arteries and atrial switch surgery, age 37.3±7.8, 37.1% female, in order to assess the prevalence and characteristics of late‐onset PH and explore associated factors. Patients were followed for a median of 32.3 years after atrial switch surgery and 10.0 years after their first referral visit. PH was detected in 18 of 33 (54.5%) patients who had invasive hemodynamic studies. Average age at diagnosis of PH was 33.9±8.1 years. PH was postcapillary in all, with a mean pulmonary artery pressure of 36±12 mm Hg and mean pulmonary capillary wedge pressure of 28±8 mm Hg. PH was diagnosed in 13 of 17 (76.5%) patients who had cardiac catheterization for heart failure or decreased exercise tolerance. In multivariable analyses, systemic hypertension (odds ratio 9.4, 95% confidence interval 2.2‐39.4, P =0.002) and heart failure or New York Heart Association class III or IV symptoms (odds ratio 49.8, 95% confidence interval 8.6‐289.0, P <0.001) were independently associated with PH. Patients with PH were more likely to develop cardiovascular comorbidities including atrial ( P =0.001) and ventricular ( P =0.008) arrhythmias, require hospitalizations for heart failure ( P <0.001), and undergo tricuspid valve surgery ( P <0.001). Mortality was significantly higher in patients with PH (hazard ratio 9.4, 95% confidence interval 2.1‐43.0], P <0.001). Conclusions: Late‐onset postcapillary PH is highly prevalent in adults with transposition of the great arteries and atrial switch surgery and is associated with an adverse prognosis.